Girls Get Free Drinks: Undergraduates' Misunderstandings of Heterosexual Privilege. Issue 12 (15th October 2017) - Nunn, Lisa M.; Sgoutas-Emch, Sandra; Sumner, Steven; Kirkley, Evelyn
ABSTRACT: Heterosexual privilege is a challenging concept to teach in undergraduate courses. Using data from self-reflection essays on the first and last days of the semester, we present students' learning and growth in their understanding of heterosexual privilege and their ability to distinguish it from cisgender privilege. The majority of students accurately identified an instance of heterosexual privilege in their lives and discussed the counterpart to privilege: the marginalization and/or disenfranchisement experienced by individuals who hold other sexual identities. This article highlights the two most common misunderstandings of heterosexual privilege that emerged in students' writing. On the first day of class, 18.2% outright denied that heterosexual privilege exists, and 17.6% conflated gender with sexuality. It reduced to 11.9% and 11.3%, respectively, on the last day of class. We saw growth in students' sophistication of perspective even for some students who demonstrated these misunderstandings at the end of the term.